2018
DOI: 10.14236/ewic/hci2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance Analysis of a Commercial Wearable EOG Glasses for an Asynchronous Virtual Keyboard

Abstract: Conventional electrooculography (EOG) signal acquisition systems, apart from requiring expensive equipment, necessitate electrode gel for conductivity and electrode wires, which may obstruct the field of view and restrict user movements, thus making the setup itself impractical for regular use. Recently however, a cheaper, wireless, gel-free, sleek and wearable alternative EOG recording device, inconspicuously incorporating dry electrodes mounted on an ordinary-looking pair of glasses, has been made commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…3 Values smaller than 5% of the maximum value of p-MFDEOG obtained at a specific angle were considered outliers and also removed. 4 Through this, the maximum and minimum values among p-MFDEOGs were obtained, and this was repeated for all angles. In this study, the threshold values were found in the order from smallest to largest.…”
Section: Individual Threshold-based Eog Signal Classification Of the ...mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Values smaller than 5% of the maximum value of p-MFDEOG obtained at a specific angle were considered outliers and also removed. 4 Through this, the maximum and minimum values among p-MFDEOGs were obtained, and this was repeated for all angles. In this study, the threshold values were found in the order from smallest to largest.…”
Section: Individual Threshold-based Eog Signal Classification Of the ...mentioning
confidence: 99%
“…This method has the advantage of increasing the user's convenience by using a single channel dry electrode sensor, but can recognize only a double-blink action. Barbara et al [4] compared a commercial wearable EOG acquisition system called "JINS MEME EOG glasses" that can acquire EOG signals in the form of wearable glasses with a conventional standard EOG acquisition system. According to the performance evaluation through the virtual keyboard interface, their system was very simple compared to the conventional gel-based wired acquisition system, although the writing speed showed only a small difference of 2 characters/min.…”
Section: Introductionmentioning
confidence: 99%
“…These electrodes are gel-free and, therefore, represent an advantage compared to conventional EOG signal acquisition systems, which require gel for conductivity. 26 Tag et al. 23 used EOG glasses to identify fatigue in real-life daily activities over 14 days.…”
Section: Eye-tracking Systems’ Feasibility In the ...mentioning
confidence: 99%
“…In contrast, when investigated in labor contexts, eye trackers have been found to achieve good reliability in eye-movement tracking. 19 , 26 , 29 Evidently, the performance gap between tracking eye movements in controlled or unnatural settings and tracking such movements in unconstrained operational environments is considerable. To implement these systems in real-life settings in order to monitor fatigue levels, several challenges must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, basic deliberate eye movements such as saccades (i.e., fast eye movements), fixations (i.e., the duration between two saccades when the gaze is fixated at a point), and blinks have been used for hands-free operation in HCI and human-machine interfaces (HMIs) [11]. With the help of HCI and HMIs one can emulate a computer mouse [12], type using a virtual keyboard [13], drive a wheelchair or control a robotic arm [14], change TV channels [15], and even improve user experience on virtual reality gaming [16] or smartphone operation [17]. Along these lines, in the healthcare domain, as part of a hospital alarm system, EOGbased switches provided immobile patients with a safe and reliable way of signaling an alarm [18].…”
Section: Introductionmentioning
confidence: 99%